Motivation for the practice and maintenance in high level Gymnastics - Lopes, Priscila (2007)
In Women Gymnastics (WG) many coaches believe that early specialization is needed to reach the high level. Then, WG requires special attention regarding the motivation of the athletes in order to prevent dropout from training when they are just reaching a high performance level in their sporting career. The objective of this study was to investigate the factors that motivate girls to the practice of the G in the high level. Twenty gymnasts between 11 and 14 years of age were interviewed. The results revealed that the intrinsic motivation of the gymnasts are closely related to the enjoyment of the activity, to the desire of being committed to WG up to their physical limits, and to the pleasure of training after a successful competitive season. In respect to the extrinsic motivation it was clear that gymnasts search for important titles, the maximum effort during the competitions for better performance, and the motivation for training after unsuccessful competitive seasons in order to avoid similar mistakes in the following events. The results suggest that coaches should know and consider these factors in order to design motivational strategies aiming at preventing high level gymnasts from dropout of the sport.